The role of residential distributed energy resources in Pakistan's energy transition. (August 2022) - Mehmood, Fahad; Umar, Muhammad; Dominguez, Cristina; Kazmi, Hussain
Abstract: In light of climate change concerns and falling costs, many low-income countries, such as Pakistan, have adopted a number of policies to incentivise distributed energy resources and generation. These policies have meant that the installed base of grid-connected distributed solar generation in Pakistan has grown rapidly, from only 1 MW in 2015–2016 to 232 MW in 2020–2021. However, it still constitutes a paltry 0.5% of the overall electricity mix. In this paper, using high-resolution demand and generation profiles from Lahore (the second most populous city in Pakistan and the one with the most distributed generation), we show that distributed generation offers low payback periods for urban households, even without net metering. This calculus is aided by likely future tariff hikes. Additionally, distributed generation helps support the grid, even without storage or demand response, due to a close alignment between supply and demand. Based on this analysis, we recommend the regulator to provide longer term visibility on the continuation of incentives such as net metering, and how this will eventually be shifted towards solar mandates. Likewise, it is prudent for distribution companies to provide targeted incentives for uptake of distributed generation to alleviate issues such as non-technical losses and transformer overloading. Highlights: DERs offer an attractive investment for households in Pakistan, even without net-metering. Self-consumption rates, even without local storage, can exceed 80% in certain conditions. Distributed generation with battery storage reduces peak load on low-voltage distribution grid. Given proper incentives, DERs will play an important role in the energy transition.